Gender Dalam Pengaruh Literasi Keuangan Digital dan Kondisi Psikologis Terhadap Perilaku Manajemen Keuangan Mahasiswa - Lilavita Dina Setyawati; Vicky Vendy (Forum Kerjasama Pendidikan Tinggi, 2026)
The advancement of financial technology empowers students to handle money effectively through the use of digital services. However, financial management is impacted not just by digital currency literacy but also by individual psychological conditions. The study's goal is to demonstrate how digital literacy, locus of control, and self-ability support the management of a mahasiswa's finances and challenge gender norms in addressing these issues. This study is quantitative and uses primary data. The subject of the study is a D1 and S1 student in university in Surabaya, which has a population of about 159.590. The minimal sample size of 100 responders was established using the Slovin formula. 220 individuals filled out the online survey that was provided. The SmartPLS4 application was used to process the data using the SEM-PLS approach. The findings indicated that self-efficacy (β=0.344; t=3.223; p=0.001) and digital financial literacy (β=0.383; t=3.755; p<0.001) significantly improved financial management behavior. There was no significant impact from the internal locus of control (p=0.343) or the external locus of control (p=0.417). Gender did not moderate the relationship, according to the results of the gender moderation test utilizing the Multi-Group Analysis approach, which revealed that there was no difference in the influence between genders on all association pathways (p>0.05). By analyzing the impact of digital financial literacy and conditions and highlighting the role of gender in moderating the relationship, this study adds to the body of knowledge on student financial management behavior.